Racial/ethnic health disparities among children with special health care needs in Boston, Massachusetts. Issue 3 (July 2022) - Dembo, Robert S.; LaFleur, Jennifer; Akobirshoev, Ilhom; Dooley, Daniel P.; Batra, Neelesh; Mitra, Monika
Abstract: Background: Little is known about the factors that contribute to racial/ethnic disparities among children with special health care needs (CSHCN). Objective: To quantify the contributions of determinants of racial/ethnic disparities in health and health care among CSHCN in Boston, Massachusetts. Methods: A sample of 326 Black, Latino, and white CSHCN was drawn from the Boston Survey of Children's Health, a city-wide representative sample of children. The study implemented Oaxaca–Blinder-style decomposition techniques to examine the relative contributions of health resources and child-, family-, and neighborhood-level factors to disparities in four outcomes: health status, barriers to medical care, oral health status, and utilization of preventive dental care. Results: White CSHCN had a greater likelihood of having very good/excellent health and oral health and were less likely to experience barriers to care than Black CSHCN. Compositional differences on predictors explained 63%, 98%, and 80% of these gradients, respectively. Group variation in household income, family structure, neighborhood support, and exposure to adverse childhood experiences accounted for significant portions of the Black–white gaps in health and access. White CSHCN were also more likely to have very good/excellent health and oral health compared to Latino CSHCN. Differences on predictors accounted for about 86% and 80% of these gaps, respectively. Household income, adverse childhood experiences, and household language emerged as significant determinants of Latino–white disparities. Conclusions: Racial/ethnic health disparities among CSHCN are explained by relatively few determinants. Several of the contributing factors that emerged from the analysis and could be targeted by public health and policy interventions. Highlights: Prior research has documented racial/ethnic disparities in health among children with special health care needs (CSHCN). Little is known about the pathways that lead to health inequities in this population. Using decomposition methods, this study identifies factors that contribute to disparities among CSHCN in Boston. Among CSHCN, racial/ethnic disparities in health are primarily driven by social determinants. Interventions that address children's social contexts, and not just health care resources, are needed to reduce disparities.